ANALISIS COST VOLUME PROFIT PADA HOTEL ROYAL VICTORIA SANGATTA - Hilman, Hilman (EKONOMIA, 2013)
Hilman . , 2013. Cost Volume Profit Analysis at the Royal Victoria Sengata , under the guidance of Mr. Robin Jonathan and Mrs. ElfredaA.Lau.This study aims to determine the break even point Hotel Royal Victoria Sengata with the achievements of the room occupancy rate held during the last 3 years ie 2010 to 2012 and to determine the limit of the percentage reduction in the volume of sales that the company still makes a profit .Formulation of the problem in this study is 1 . Is the achievement level of occupancy owned , Hotel Royal Victoria has reached break-even ? and 2 . How much % of sales volume may be lowered so Hotel Royal Victoria still make a profit ? . The hypothesis in this study are: 1 . Allegedly the achievement of current occupancy levels , Royal Victoria has reached Break Event , and 2 . If the production volume is reduced by 10 % then the Hotel Royal Victoria still makes a profit .Analysis and hypothesis testing tools used are the Cost Volume Profit Analysis , which covers Break Even Point and Margin of Safety .The analysis showed that the break-even point Hotel Royal Victoria in 2010 amounted to Rp9,733,736,186 , in 2011 amounting to Rp 8,954,767,021 and Rp 8,326,026,681 in 2012 , which means that the Hotel Royal Victoria has reached break-even with the achievements of the occupancy rate owned .Margin of Safety Hotel Royal Victoria in 2010 by 33 % , in 2011 by 29 % and in 2012 by 49 % . This suggests that if the sales volume is reduced by 10 % then the Hotel Royal Victoria still makes a profit .The analysis results show that the hypothesis on Hotel Royal Victoria Sengataaccepted .